2021
DOI: 10.1186/s12889-021-10736-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sufficient MVPA among Thai adults: pooled panel data analysis from Thailand’s surveillance on physical activity 2012–2019

Abstract: Background The role of data in informing decision makers in formulating policy to improve population health is undeniably important. During the past few years, the Thai government has undertaken continuous health promotion campaigns and programs. Nevertheless, evidence of how physical activity (PA) has improved is lacking. This study aims to present PA prevalence and trends from nationally-representative surveillance data collected during 2012–2019. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Regional disparities are reflected by a higher level of inactivity among Latin American, Central Asian, and northern-hemisphere countries [ 1 ]. Previous studies in Thailand also reported that the PA level of Thais differed according to age, sex, geographical region, residential area (urban/rural), educational attainment, and occupation [ 19 ]. PA participation was also correlated with physical and social environment of the individual, including family, peers, and the availability of facilities and information [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regional disparities are reflected by a higher level of inactivity among Latin American, Central Asian, and northern-hemisphere countries [ 1 ]. Previous studies in Thailand also reported that the PA level of Thais differed according to age, sex, geographical region, residential area (urban/rural), educational attainment, and occupation [ 19 ]. PA participation was also correlated with physical and social environment of the individual, including family, peers, and the availability of facilities and information [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the data from two Thailand’s Surveillance on Physical Activity surveys showed a fluctuating trend. They found that Thai adults (aged 18 years and over) engaged in moderate-to-vigorous PA on average for 11.7 h/week in 2012, 13.8 h/week in 2013, 11.2 h/week in 2014, and 9.1 h/week in 2015 [ 80 ]. If we only consider the first and the last year in their survey, our findings are in accordance with their results.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy diet and physical activity promotions are active campaign since 2001 by Thai Health Foundation 43. Thailand may capitalise the high prevalence of adequate moderate-to-vigorous physical activities and many WHO recommended NCD measures implemented, such as sugar sweetened beverages tax, strengthening food environment, regulation of food marketing, alcohol and tobacco control 44–47. However, significant efforts are required to reverse the worsening prevalence trend.…”
Section: Discussionmentioning
confidence: 99%